BUS AND EMBEDDED SYSTEM DESIGN OF A 2U CUBESAT FOR MARITIME PURPOSES - Ariecintya Janita, Dhinda
CubeSat or Cube Satellite is a nano satellite that is deployed on LEO. Compared to GEO satellites, CubeSat has cheaper production cost, shorter manufacturing time, and low complexity. A CubeSat usually only able to have one mission because of its small size. There are various missions that could be conducted by a CubeSat, such as detecting sailing vessels in the Indonesian territory using the AIS (Automatic Identification System). By using CubeSat as an AIS receiver all of Indonesian maritime territory could easily be covered. The aim of this final project is to design a CubeSat based on the standard that could held every component that are needed in order to receive the AIS signal. The design of the CubeSat structure is done using the SolidWorks software. The CubeSat will only receive AIS data while orbiting above Indonesia. This setting is done by using a scheduling system on the on-board computer Banana Pi M2+. The scheduling is done using bash script by dividing the CubeSat activities into four modes, the activation mode, data receiving mode, data transmitting mode, and the memory cleaning and idle mode. The duration of each mode is determined by the orbital period of CubeSat and the duration of CubeSat when above Indonesian territory. Based on the evaluation and tests, the CubeSat 2U has a dimension of 10 x 10 x 22 centimeters with a mass of 930.8 grams. The dimension and mass of the designed CubeSat 2U is in accordance with the standard by CDS (CubeSat Design Specification). The on-board computer Banana Pi M2+ also able to manage the CubeSat so the CubeSat can receive AIS data, take pictures, send AIS data and the pictures taken, and cleans its memory according to the duration of the CubeSat is in the Indonesian territory for 7 minutes with an orbital period of 92 minutes.